Remarkable Enhancement of Catalytic Activity of Cu‐Complexes in the Electrochemical Hydrogen Evolution Reaction by Using Triply Fused Porphyrin. Issue 1 (14th December 2022) - Chandra, Shubhadeep; Hazari, Arijit Singha; Song, Qian; Hunger, David; Neuman, Nicolás. I.; van Slageren, Joris; Klemm, Elias; Sarkar, Biprajit
Abstract: A bimetallic triply fused copper(II) porphyrin complex (1 ) was prepared, comprising two monomeric porphyrin units linked through β–β, meso – meso, β′–β′ triple covalent linkages and exhibiting remarkable catalytic activity for the electrochemical hydrogen evolution reaction in comparison to the analogous monomeric copper(II) porphyrin complex (2 ). Electrochemical investigations in the presence of a proton source (trifluoroacetic acid) confirmed that the catalytic activity of the fused metalloporphyrin occurred at a significantly lower overpotential (≈320 mV) compared to the non‐fused monomer. Controlled potential electrolysis combined with kinetic analysis of catalysts 1 and 2 confirmed production of hydrogen, with 96 and 71 % faradaic efficiencies and turnover numbers of 102 and 18, respectively, with an observed rate constant of around 10 7  s −1 for the dicopper complex. The results thus firmly establish triply fused porphyrin ligands as outstanding candidates for generating highly stable and efficient molecular electrocatalysts in combination with earth‐abundant 3d transition metals. Abstract : Triple threat : Bimetallic triply fused copper containing metalloporphyrin (1 ) displays excellent activity towards electrochemical proton reduction. The activity is far better compared to its monomeric counterpart (2 ).